Pengaruh Tingkat Penghasilan dan Kesadaran Wajib Pajak Terhadap Kepatuhan Membayar PBB di Kecamatan Tegal Barat - Canesya Helga Rianti; Sriniyati Sriniyati (Jurnal Literasi Akuntansi, 2026)
Purpose: This study aims to analyze the influence of taxpayer income and taxpayer awareness on the level of compliance in paying Land and Building Tax in West Tegal District, Tegal City Method: This study used quantitative approach with data collection technique through questionnaire, distributed to 53 taxpayers in West Tegal District, Tegal City Finding: The results of the study indicate that taxpayer income partially has a significant effect on compliance in paying PBB, while taxpayer awareness is also proven to have a positive and significant effect on the level of compliance. Simultaneously, taxpayer income and awareness significantly influence taxpayer compliance in paying Land and Building Tax Novelty: The inconsistency in previous research findings constitutes a research gap that warrants further investigation. In addition, West Tegal District has distinctive characteristics compared to other regions examined in prior studies. Therefore, conducting this study is considered necessary.